Novel mRNA therapy restores GALT protein and enzyme activity in a zebrafish model of classic galactosemia. Issue 4 (27th May 2022) - Delnoy, Britt; Haskovic, Minela; Vanoevelen, Jo; Steinbusch, Laura K. M.; Vos, Esther Naomi; Knoops, Kèvin; Zimmermann, Luc J. I.; Noga, Marek; Lefeber, Dirk J.; Martini, Paolo G. V.; Coelho, Ana I.; Rubio‐Gozalbo, Maria Estela
Abstract: Messenger RNA (mRNA) has emerged as a novel therapeutic approach for inborn errors of metabolism. Classic galactosemia (CG) is an inborn error of galactose metabolism caused by a severe deficiency of galactose‐1‐phosphate:uridylyltransferase (GALT) activity leading to neonatal illness and chronic impairments affecting the brain and female gonads. In this proof of concept study, we used our zebrafish model for CG to evaluate the potential of human GALT mRNA ( hGALT mRNA) packaged in two different lipid nanoparticles to restore GALT expression and activity at early stages of development. Both one cell‐stage and intravenous single‐dose injections resulted in hGALT protein expression and enzyme activity in the CG zebrafish ( galt knockout) at 5 days post fertilization (dpf). Moreover, the levels of galactose‐1‐phosphate (Gal‐1‐P) and galactonate, metabolites that accumulate because of the deficiency, showed a decreasing trend. LNP‐packaged mRNA was effectively translated and processed in the CG zebrafish without signs of toxicity. This study shows that mRNA therapy restores GALT protein and enzyme activity in the CG zebrafish model, and that the zebrafish is a suitable system to test this approach. Further studies are warranted to assess whether repeated injections safely mitigate the chronic impairments of this disease. Abstract :